Adaptation in the Age of Media Convergence - Schäfke-Zell, Werner; Fehrle, Johannes (Book collections on Project MUSE., 2019)
This collection considers new phenomena emerging in a convergence environment from the perspective of adaptation studies. Giving an overview of the various fields and practices most prominent in convergence culture and viewing them as adaptations in a broad intertextual and intermedial sense, the contributions offer reconsiderations of theoretical concepts and practices in participatory and convergence culture. These range from fan fiction born from mash-ups of novels and YouTube songs to negotiations of authorial control and interpretative authority between media producers and fan communities to perspectives on the fictional and legal framework of brands and franchises. In this fashion, the collection expands the horizons of both adaptation and transmedia studies and provides reassessments of frequently discussed (BBC's Sherlock, the Alien franchise, or LEGO) and previously largely ignored phenomena (self-censorship in transnational franchises or YouTube cover videos).